2022
DOI: 10.1007/s40279-022-01692-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-Exercise Caffeine Intake on Endurance Performance and Core Temperature Regulation During Exercise in the Heat: A Systematic Review with Meta-Analysis

Abstract: Background: Heat is associated with physiological strain and endurance performance (EP) impairments. Studies have investigated the impact of caffeine intake upon EP and core temperature (CT) in the heat, but results are conflicting. There is a need to systematically determine the impact of pre-exercise caffeine intake in the heat.Objective: Use a meta-analytical approach to determine the effect of pre-exercise caffeine intake on EP and CT in the heat.Design: Systematic review with meta-analysis.Data sources: F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…DITI was performed using the Iris-XP Digital infrared imaging system (Medicore, Seoul, Republic of Korea). Volunteers scheduled for DITI were informed about general precautions such as avoiding exposure to cold or hot environments, not smoking, and not consuming caffeine for 1 h before the test [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…DITI was performed using the Iris-XP Digital infrared imaging system (Medicore, Seoul, Republic of Korea). Volunteers scheduled for DITI were informed about general precautions such as avoiding exposure to cold or hot environments, not smoking, and not consuming caffeine for 1 h before the test [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the previous meta-analytical findings support this observation and have been corroborated further by a recent meta-analysis, which demonstrated a 0.1°C/h greater Tcore rate of rise following caffeine supplementation (Naulleau et al, 2022). Overall, this suggests that caffeine has an undesirable (i.e.…”
Section: Caffeinesupporting
confidence: 55%
“…Although these factors ensure the internal validity of these laboratory studies, they limit their ecological validity. For example, a recent meta‐analysis has shown that caffeine ingestion before exercise in the heat significantly increases the rate of change in core temperature 101 . There was a large variability in how work intensity was reported, which does not allow for an adequate synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent meta-analysis has shown that caffeine ingestion before exercise in the heat significantly increases the rate of change in core temperature. 101 There was a large variability in how work intensity was reported, which does not allow for an adequate synthesis. We recommend harmonizing the reporting of work intensity by reporting the metabolic rate in W or kcal/h, as recommended by current guidelines.…”
Section: Limitations For Testing the Effectiveness Of Work-rest Regim...mentioning
confidence: 99%